Tendencies in Noun Stress in the Southern Aukštaitian Subdialects in Handwritten Sources of the 1950s and 1960s - Ragaišienė, Vilija (Respectus Philologicus, 2012)
The article deals with variously stressed nouns that were discovered in the 1950s and 1960s in handwritten sources of the southern Aukštainian subdialects in the archive of dialects of the Language History and Dialectology Department of the Institute of the Lithuanian Language. Data on the nouns and noun forms of the southern Aukštaitians, collected from almost the entire area under study, i.e., fifty-five inhabited settlements, demonstrate two tendencies: stress variance and oxytogenesis.Summarising the collected data, it was established that nouns with the same stem (o, io, ā, ē, ā, i, u and u) are most often stressed in two ways in the southern Aukštaitian area, e.g., kaklas (2/4), žmogùs (4) / žmõgus (2), and others.Words with non-productive i, u, u and consonant stems can also have separate parallels with other stems, or parallel forms of other separate stems, e.g.: vags (4), sing. gen. vagiẽs / vãgio, cf. nom. vãgys / vagia, šuvà (4), sing. gen. šuñs / šunès / šuniẽs / šùnio, etc.The abundance of the variants discovered in these handwritten sources of rather small volume demonstrates the intensity of stress variance in the southern Aukštaitian area in the 1950s and 1960s, which is corroborated by two facts. First, most of the forms of the words with variable stress in the sources under study appear several or even many times. Second, quite a few forms of such nouns were discovered within the same subdialect. Despite all this, nouns in the southern Aukštaitian subdialects are not stressed interchangeably, but according to one accentual paradigm. From two stress variants used in the subdialects, one is main, the other a parallel variant. The nouns in the handwritten sources are stressed in two ways, most often according to the paradigms of stem and mobile accentuation, e.g., bróliai / brolia, sõdžius (2) / sodžiùs (4), etc. The appearance of nouns with dual stress in the southern Aukštaitian subdialects and the tendency towards oxytogenesis are primarily related to the accentual and semantic models of two plurals, simple and collective, which are being reconstructed, e.g., pelis, pl. peliai / collect. pl. peilia.The stress on the singular instrumental endings and/or of the plural accusative forms of nouns with acute stems might also be related to the collective plural. The existence of such forms can be determined by the levelling of the accentual paradigm, cf., pėda, pėd, pėdám(s), pėdùs, pėdas. The possibility that the discussed forms could have been inherited, i.e., could have originated from the oxytonic paradigm, should not be discounted. Undoubtedly, noun accentuation might have been influenced by the factors of stem interaction: the existence of homonymous forms, levelling of the morpho(no)logic paradigm, the conformity of the system, etc. There is also no doubt that the accentuation analogue had an influence as well (especially that of productive stems on unproductive ones).
Keywords: accentual variant; stress variance; oxytogenesis; simple and collective plural; stem